Hypocalcemic Rachitic Stridor: A Neglected Warning Sign in Infants - Abdelwahab TH Elidrissy; Jalal S Babekir (Global Journal of Rare Diseases - Peertechz Publications, 2017)
Although stridor is a common respiratory symptom associated with upper respiratory diseases, yet its relation with hypocalcemia is not widely appreciated. The mechanism of hypocalcemia in causing stridor might be a collapsing of larynx most likely caused by decalcification due to hypocalcemia. Vitamin D     deficiency causes a reduction in serum calcium, which stimulates the production of extra PTH to mobilize and maintain calcium from bone and cartilage for more vital cells of the body, brain, heart and blood. Stridor might appear with upper respiratory tract infection, accordingly the role of hypocalcemia as a cause of stridor might not be recognized. Infants are born with poor vitamin D in places with high prevalence of vitamin D deficiency due to environmental, social, customs and housing factors. Due to maternal vitamin D deficiency, breast milk is low in vitamin D which leads to poor absorption of calcium. Stridor caused by hypocalcemia should be considered as a warning sign to prevent more serious complications as cardiomyopathy, myelofi brosis, and convulsions. In communities with high prevalence of vitamin D defi ciency checking for hypocalcemia should be part of the work up, when stridor is the presenting symptom in infants. The mechanism by which hypocalcemia causes stridor might be laryngiomalacia.